Good refugees, bad migrants? Stereotype content, threat perception and helping orientations towards refugees, migrants and economic migrants in Germany - Wyszynski, Mia Caroline (2019)
The present study examined the effect of group labels on social perception and helping behavioral intentions towards displaced people in Germany. Specifically, it examined whether activating different social categories to refer to displaced people impacts threat perceptions among host society members, as well as, their autonomy and dependency helping orientations towards the newcomers. Participants (N = 304) were randomly assigned to one of the three conditions (refugee vs. migrant vs. economic migrant) and read fabricated case vignettes, featuring a displaced person who arrived to Germany recently. Results indicate that, as predicted, the use of different group labels impacts stereotypes held by host society members, as well as their helping orientations. While the label refugees triggered paternalistic stereotypes and evoked dependency-oriented helping intentions, the label economic migrants elicited envious stereotypes and a decrease in help affirmation. Consequences and practical implications to strengthen peaceful intergroup relations between host society members and newcomers are discussed.